PROGRAM KEMITRAAN MASYARAKAT INOVASI RESERVE ENERGY HYBRID (WIND TURBINE, SOLAR CELL DAN GENERATOR) DI PEMERINTAH DESA TEGAL SAMBI KABUPATEN JEPARA - Safrizal Safrizal; Gunawan Muhammad; Noor Azizah; Darnoto Darnoto; Dimas Ariyanto; Vania Rizka Amelia (Yayasan Education and Social Center, 2022)
This service activity aims to assist service partners in optimizing the surrounding natural resources and financial efficiency of village government institutions. In addition, this activity also aims to help the central government in order to reduce the use of fossil fuel electrical energy by maximizing the use of solar and wind heat which is very abundant in the village of Tegalsambi Tahunan Jepara. To realize the purpose and purpose of holding this service activity, the team provided several solutions which include the following things 1) making a hybrid solar cell power plant design that will be placed in the Tegal Sambi village hall as an effort to efficiently use PLN electricity so that it is expected to reduce the cost of electricity use at the village service office. This activity is made with five stages, namely analyzing the needs of energy use, designing solar cell power plants, socialization to village governments and communities, installation and installation of solar cell power plants, as well as assistance in use and maintenance. 2) manufacture and installation of wind power plants (wind turbines) on public street lighting (PJU)